EFFECT OF COOPERATIVE TEACHING METHOD ON ACADEMIC ACHIEVEMENT OF MALE AND FEMALE OFFICE TECHNOLOGY AND MANAGEMENT STUDENTS IN BUSINESS COMMUNICATIONS IN POLYTECHNICS (NAU Journal of Technology and Vocational Education, 2024)
This study investigated the effect of cooperative teaching method on male and femaleoffice technology and management students’ achievement in business communicationin selected polytechnics in South-East Nigeria. Two research questions guided thestudy while two null hypotheses were tested at 0.05 level of significance. The studywas quasi-experimental which used pre-test, post-test non-randomized group design.The population of the study consisted of 608 office technology and managementstudents while the sample size was 214 students drawn through simple randomsampling technique. A validated Business Communication Achievement Test (BCAT)containing 40 items was used for data collection. The reliability of the instrument wasdetermined by administering the test instrument on a group of 30 students who werenot part of the study sample. Kuder Richardson 20 (KR-20) was used to establish thereliability of the instrument to check for internal consistency of test items withdichotomous choices. A reliability coefficient of 0.74 was obtained. The arithmeticmean was used to analyze data in respect of the research questions while ANCOVAwas used to test the hypotheses. Findings indicated that there was no significantdifference in the mean achievement scores of male and female students taught withcooperative teaching method. There was no significant interaction effect betweenteaching method and gender on students’ achievement in business communication. Itwas concluded that cooperative teaching method enhanced both male and femalestudents’ academic achievement in business communication than the lecture method.The implication of the study is that integration of cooperative teaching method byOTM lecturers will improve students’ academic achievement. Consequently, it wasrecommended among others that OTM lecturers should use cooperative teachingmethod in teaching business communication.
Keywords: Cooperative Teaching method, Office technology and Management, Business Communication, Academic Achievement